Consumers' perception of the warmth and competence of design-imitating companies. Issue 2 (4th May 2017) - Ahn, Minyoung; Lee, Joeun; Lee, Yuri
ABSTRACT: The incidence of unethical conduct, whereby large companies imitate small companies' product designs, is increasing. This study examined the way in which market leadership affected perceived warmth and competence with respect to design-imitating companies and investigated the relationships between these perceptions and consumer attitudes and behaviour. The results showed that reductions in perceived warmth and competence were significantly greater when market-leading companies copied small companies' designs than they were when small companies copied leader's designs. Attitudes towards the design-imitating company mediated the relationship between perceived warmth and competence and intention to purchase the imitation product. Consumers' ethical consciousness moderated the relationship between their psychological perception and attitudes towards imitators. The results advanced understanding of the impact of design imitation by considering companies' market leadership and introducing the concepts of perceived warmth and competence to clarify psychological reasons for purchasing imitation products.